2011
DOI: 10.1128/jcm.01443-10
|View full text |Cite
|
Sign up to set email alerts
|

Using Molecular Epidemiology To Trace Transmission of Nosocomial Norovirus Infection

Abstract: Nosocomial norovirus (NoV) infection is common and may lead to complications in vulnerable hospitalized patients. Understanding sources and modes of transmission of noroviruses within health care settings will support the design of evidence-based strategies for reducing introduction and further spread. We sequenced a highly variable segment of the genome to identify possible clusters in patients with and without acute gastroenteritis who were hospitalized in the period 2002-2007. Admission and sampling dates w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 26 publications
1
38
1
Order By: Relevance
“…Although NoV GII.17 seems to be prevalent in some parts of Africa this genotype was not identified in clinical specimens (Silva et al 2008;Abugalia et al 2011;Hassine-Zaafrane et al 2013;Huynen et al 2013;) and environmental samples (Sdiri-Loulizi et al 2010) from many other African regions and the GII.17 predominance appears to be peculiar to Kenya. Norovirus GII.17 is of clinical relevance as it has been implicated in nosocomial NoV infection (Sukhrie et al 2011) and chronic NoV infection in a kidney transplant patient (Schorn et al 2010). The genotype has also been widely reported in children with gastroenteritis in Central and South America (Bucardo et al 2009;Ferreira et al 2012;Gomes et al 2008), Korea (Park et al 2011) and Thailand (Kittigul et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Although NoV GII.17 seems to be prevalent in some parts of Africa this genotype was not identified in clinical specimens (Silva et al 2008;Abugalia et al 2011;Hassine-Zaafrane et al 2013;Huynen et al 2013;) and environmental samples (Sdiri-Loulizi et al 2010) from many other African regions and the GII.17 predominance appears to be peculiar to Kenya. Norovirus GII.17 is of clinical relevance as it has been implicated in nosocomial NoV infection (Sukhrie et al 2011) and chronic NoV infection in a kidney transplant patient (Schorn et al 2010). The genotype has also been widely reported in children with gastroenteritis in Central and South America (Bucardo et al 2009;Ferreira et al 2012;Gomes et al 2008), Korea (Park et al 2011) and Thailand (Kittigul et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…This complex pattern of strain coexistence again contrasts with the case for the noroviruses, for which individual genotypes predominate in any given season. Most notably, genotype II.4 has comprised 44% of 773 norovirus outbreaks in the United States over a 12-year period (1994 to 2006), with 51 to 85% of recent outbreaks being associated with GII.4 (46,48,53). The national and international epidemiological dominance of genotype II.4 has been attributed to a higher error rate of its viral RNA polymerase and an associated higher rate of evolution within the virus capsid (2).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we did not address undiagnosed NoV infections among hospital personnel, although recent studies have indicated that infected personnel can play an important role in the NoV transmission chain (16). Hence, appropriate collection and testing in both patients and personnel will be required for developing new evidence-based strategies to prevent the introduction and spread of NoV (20).…”
Section: Discussionmentioning
confidence: 99%
“…cDNA was amplified by a seminested PCR, and subsequently, region A of the polymerase gene was sequenced using the ABI-Prism BigDye Terminator v3.0 ready reaction cycle kit (ABI Prism 7700 sequence detection system; Applied Biosystems, Foster City, CA) as described previously (20). Sequences were assembled in BioNumerics (Applied Maths, Sint-Martens-Latem, Belgium, software package 6.6.4), evaluated manually for their quality by looking for the number of ambiguities, errors, mismatches, and deletions, and genotyped with an NoV-genotyping tool (http://www.rivm.nl/mpf/norovirus /typingtool) (13).…”
Section: Methodsmentioning
confidence: 99%